The Archive of the Counts of Medellín, “Royal Wardrobes” of the Castilian crown - Sánchez González, Antonio (Revista General de Información y Documentación, 2020)
This paper aims to analyze a collection of documents found in the “Medellín” section of the Medinaceli Dukal Archive, a large collection of over several hundred documents involving the county of Medellín, Extremadura. This collection was owned by the Portocarrero House, who worked as Royal Wardrobes for the kings of Castile since the Middle Ages and who had clear Portuguese connections.From the 17th century onwards, the Counts of Medellín related to other noble houses in Spain, which made their Archive pass into the hands of the Dukes of Santisteban del Puerto during the 18th century and, later, into the hands of the Dukes of Medinaceli in 1818 definitely. The documents which formed the so-called Medellín section come from the two houses we have just referred to, as this paper discovers.
Keywords: Portocarrero House; Counts of Medellín; Royal Wardrobes; Kingdom of Castille; Medinaceli Dukal Archive